Prevalence of emotional and behavioral problems among school-going adolescents: A cross-sectional study - U Harikrishnan; Grace Lalhlupuii Sailo (Wolters Kluwer Medknow Publications, 2021)
Background: Adolescence is a period of several emotional, mental, and behavioral changes, and many adolescent problems are manifested in the form of emotional problems, conduct problems, hyperactivity, and peer-related problems. The objectives of the current study are to assess the prevalence of emotional and behavioral problems across gender and location. It analyzes the Strengths and Difficulties Questionnaire (SDQ) total score with sociodemographic details among school-going adolescents in Kollam district. Materials and Methods: A cross-sectional study of 600 school-going adolescents between Class VIII to XII from the rural and urban areas in Kollam district was carried out using a cluster sampling method. A self-reported SDQ was administered to the respondents. Results: The findings indicate that a little more than a tenth of school-going adolescents had emotional and behavioral problems and multiple regression analysis revealed a significant association in SDQ total score with the type of schools, settings, and socioeconomic status. Conclusion: Early detection, periodical assessment, and intervention in the schools with the aid of mental health professionals can help adolescents in coping with different issues and for a healthy transition into adulthood.